(untitled) (New York, 1999)
As the definitive guide for the armchair astronomer, The New Solar System has established itself as the leading book on planetary science and solar system studies. Incorporating the latest knowledge of the solar system, a distinguished team of researchers, many of them Principal Investigators on NASA missions, explain the solar system with expert ease. The completely-revised text includes the most recent findings on asteroids, comets, the Sun, and our neighboring planets. The book examines the latest research and thinking about the solar system; looks at how the Sun and planets formed; and discusses our search for other planetary systems and the search for life in the solar system. In full-color and heavily-illustrated, the book contains more than 500 photographs, portrayals, and diagrams. An extensive set of tables with the latest characteristics of the planets, their moon and ring systems, comets, asteroids, meteorites, and interplanetary space missions complete the text. New to this edition are descriptions of collisions in the solar system, full scientific results from Galileo's mission to Jupiter and its moons, and the Mars Pathfinder mission. For the curious observer as well as the student of planetary science, this book will be an important library acquisition. J. Kelly Beatty is the senior editor of Sky & Telescope, where for more than twenty years he has reported the latest in planetary science. A renowned science writer, he was among the first journalists to gain access to the Soviet space program. Asteroid 2925 Beatty was named on the occasion of his marriage in 1983. Carolyn Collins Petersen is an award-winning science writer and co-author of Hubble Vision (Cambridge 1995). She has also written planetarium programs seen at hundreds of facilities around the world. Andrew L. Chaikin is a Boston-based science writer. He served as a research geologist at the Smithsonian Institution's Center for Earth and Planetary Studies. He is a contributing editor to Popular Science and writes frequently for other publications.
Keywords: Solar system,Hệ mặt trời